(untitled) (Global Journal of Management and Business Research, 2021)
Business managers around the globe have tested the effectiveness of the Balanced Scorecard (BSC) model since its inception in the early 90s in their bid to enhance business performance to achieve financial sustainability and transform developments in their economies. Other sectors of world economies have tried to emulate the BSC concept to achieve institutional goals for financial freedom. Research on the investigation of the replicability of the BSC model and its effectiveness in addressing the continued financial sustainability challenges of educational institutions, especially the private ones, is scarce. This study aimed to increase awareness of the influence of BSC application in addressing financial performance challenges besetting the private educational sector.